Attracting Israeli nursing students to community nursing - Yael Sela-Vilensky; Keren Grinberg; Rachel Nissanholtz-Gannot (BMC, 2020)
Abstract Background The shift from inpatient care to community patient care has had an essential impact on the nursing profession. Despite the growing demand for community nurses in many countries, their number remains relatively low and many students do not perceive this field as an interesting career to pursue. In this review we aimed to understand if exposure of undergraduate nursing students to various nursing work settings during their studies affects their work setting choices after graduation. Methods A literature search of papers relating to work setting preferences of nursing students in Israel and other countries was performed. Israel Ministry of Health, Nursing Administration documents and other related documents were also reviewed, with a focus on the nursing training program in Israel. Findings While most first-year nursing students have limited knowledge regarding the profession, in later years, their preferences for post-graduation work settings are affected by their exposure to the various clinical fields through knowledge gained in courses together with clinical practice placements. In Israel, specific classroom courses in community nursing are allocated only 6% of the total time allocated to all classroom courses in nursing, and a single clinical placement in community nursing takes place during the third or fourth year of the nursing program, exposing students to a single aspect of community nursing during their nursing training. Studies in other countries have reported that students' experience during clinical placement contributes to shaping students' opinions of nurses' roles within that field. Nursing students who had a primary healthcare placement showed greater intention for working in this setting after graduation. Conclusions The lack of exposure to the various aspects of community nursing during undergraduate studies contributes to a lack of motivation for entering this field. Therefore, a profound change is needed in nursing training programs' curricula to prepare graduates to face future challenges in community nursing. Whilst both hospital and community nursing are equally important, nursing leaders and policy makers must be made aware of the various factors that contribute to new registered nurses' preferences of hospital over community nursing and build strategies for directing nurses to work in the community in order to respond to the expected nurse shortage in this setting.